PENINGKATAN KETERAMPILAN KOLABORASI DENGAN MODEL TEAM GAMES TOURNAMENT (TGT) PADA MATA PELAJARAN MATEMATIKA KELAS V - Ambar Indraswari; Gamaliel Septian Airlanda (STKIP Subang, 2024)
The purpose of this study is to improve students’ collaboration skills on the material comparing two dimentional shape (triangle and quadrilateral) using the learning model Team Games Tournament (TGT). The low skills of student collaboration skills marked when they are discussing or working in a group, they tend to do their own duties without discussing with its group members. The subject in this study were the students of grade V of SDN Bugel 02. This study was a study of classroom actions carried out in two cycles, namely the I cycle and the II cycle, each cycle consists of planning, actions, observations, and reflection. The study instruments used are observation and documentation’s sheet. Data analysis techniques using qualitative and quantitative descriptive data analysis. Qualitative and quantitative descriptions in this study were used to describe the increase in the results of student collaboration skills. The results showed an initial 61% increase in the cycle I and improve to 85% in the cycle II. This enchancement occurred because the TGT model encouraged students to be more active during learning activity, so that their collaboration skills increased. And it can be concluded that the use of cooperative learning models TGT manages to improve collaboration skills.